Implementasi Pembelajaran PAI Melalui Daqu Method Pada Siswa di SMP Daarul Qur’an Bandung - Achmad Fauzi Fauzi; Uus Ruswandi; Bambang Samsul Arifin (Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
This research examines the implementing PAI learning through the Daqu method for students at SMP Daarul Qur'an Bandung. The objectives of this study were: to analyze the general description of the Daqu Method in Daarul Qur'an Junior High School Bandung, and to analyze how the process of implementing Islamic Religious Education learning through the Daqu Method in Daarul Qur'an Junior High School students in Bandung. . This research is a field study (field research) using content analysis. The results of this study indicate that the Daqu method in implementing Islamic Religious Education learning at Daarul Qur'an Bandung Junior High School, namely: 1 The results of his research are revealing Implementation of PAI Learning Through the Daqu Method in Junior High School Students Daarul Qur'an Bandung) Praying in congregation, in this activity there are indicators of PAI learning, a) obedience to Allah, b) have a sense of responsibility, c ) disciplined discipline, and d) comply with applicable regulations. 2) midnight prayer, dhuha, qabliyah and ba'diyah, in this activity there are indicators of Islamic education learning; a) obedience to God, b) discipline, c) responsibility. 3) The habit of zakat and sunnah fasting, in this activity there are indicators of PAI learning, including a) frugality, caring for others, empathy and generosity, b) obedience to God, honesty, and patience. 4) Al-Qur'an memorization program, in this activity there are indicators of Islamic Education learning, including: a) obeying Allah, b) being patient, c) always working hard, and d) persistence in activities and learning. 5) Learning and teaching, in this activity there are indicators of Islamic education learning, including: a) love of science, b) persistence in activities and learning, c) high enthusiasm and enthusiasm, d) independence, and e) self-confidence. . 6) Prayer, in this activity there are indicators of Islamic Education learning, including: a) tawakal to Allah, 2) qanaah attitude or willingness to accept